2016
DOI: 10.1097/cmr.0000000000000190
|View full text |Cite
|
Sign up to set email alerts
|

Neuropilin-2 promotes melanoma growth and progression in vivo

Abstract: Tumor cell interactions with their microenvironment, and neighboring endothelial cells in particular, are critical for tumor cell survival and the metastatic process. Within the spectrum of tumors, melanomas are notorious for their ability to metastasize at a relatively early stage of development; however, little is known about the molecular pathways mediating this process. We recently performed a screen to assess critical mediators of melanoma metastasis by evaluating melanoma-endothelial cell communication. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…This suggested that NRP2 expression modulated by miR-196a-3p has an effect in influencing specific steps in the metastatic cascade. Based on our finding that miR-196a-3p mimics inhibit the metastasis of breast cancer cells, which was reinforced by knockdown of NRP2 and antagonized by TGF-β1 stimulation, and previous reports that NRP2 acts as an oncogene to promote metastasis in cancers such as breast cancer [ 25 ], esophageal squamous cell carcinoma [ 26 ], and melanoma [ 27 ], we hypothesized that miR-196a-3p and its downstream target NRP2 is involved in TGF-β-induced cell migration and invasion in breast cancer. The present study provides evidence confirming the crosstalk between the TGF-β signaling pathway and miRNAs in breast cancer.…”
Section: Discussionsupporting
confidence: 56%
“…This suggested that NRP2 expression modulated by miR-196a-3p has an effect in influencing specific steps in the metastatic cascade. Based on our finding that miR-196a-3p mimics inhibit the metastasis of breast cancer cells, which was reinforced by knockdown of NRP2 and antagonized by TGF-β1 stimulation, and previous reports that NRP2 acts as an oncogene to promote metastasis in cancers such as breast cancer [ 25 ], esophageal squamous cell carcinoma [ 26 ], and melanoma [ 27 ], we hypothesized that miR-196a-3p and its downstream target NRP2 is involved in TGF-β-induced cell migration and invasion in breast cancer. The present study provides evidence confirming the crosstalk between the TGF-β signaling pathway and miRNAs in breast cancer.…”
Section: Discussionsupporting
confidence: 56%
“…Neuropilins (NRPs) function as coreceptors of the VEGF family and plexins and are involved in promoting angiogenesis and in axonal guidance, respectively ( 45 , 46 ). NRP2 was recently found to be an oncogene involved in accelerating melanoma tumor growth and progression in vivo ( 45 , 46 ). NRP2 showed significantly high expression in the primary tumors and metastatic tissues of the melanoma patient samples although normal tissues had low expression ( Figures 4A,B ).…”
Section: Resultsmentioning
confidence: 99%
“…Multiple reports have indicated a role of NRP2 in cancer metastasis. 36 For instance, NRP2 is shown to promote metastasis in melanoma 37 and to enhance migration of hepatocellular carcinoma cells. 29 In addition, NRP2 promotes metastasis in oesophageal squamous cell carcinoma through deregulation of ERK-MAPK-ETV4-MMP-E-cadherin.…”
Section: Discussionmentioning
confidence: 99%